2014
DOI: 10.1007/s00198-014-2910-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum fibroblast growth factor-23 and decreased bone turnover in patients with systemic lupus erythematosus under treatment with cyclosporine and steroid but not steroid only

Abstract: SLE patients treated with glucocorticoid and CsA exhibited markedly decreased bone turnover. Those taking CsA had higher serum FGF-23 associated with suppression of 1,25(OH)2D3 and bone formation. Such high-risk patients necessitate regular screening of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(55 reference statements)
0
5
1
Order By: Relevance
“…However, BTMs in premenopausal women with SLE have been assessed in only a few cross-sectional studies. 18,19 In the present study, although premenopausal patients with new-onset SLE showed an increase in β-CTX compared with gender-, age- and BMI-matched healthy controls, a decrease in OC and P1NP was observed, indicating an apparent uncoupling of bone remodeling in SLE patients that leads to bone loss and lower BMD.…”
Section: Discussioncontrasting
confidence: 42%
“…However, BTMs in premenopausal women with SLE have been assessed in only a few cross-sectional studies. 18,19 In the present study, although premenopausal patients with new-onset SLE showed an increase in β-CTX compared with gender-, age- and BMI-matched healthy controls, a decrease in OC and P1NP was observed, indicating an apparent uncoupling of bone remodeling in SLE patients that leads to bone loss and lower BMD.…”
Section: Discussioncontrasting
confidence: 42%
“…BMD begins to fall from the third month of glucocorticoid use and progresses rapidly to six months. From this period, the curve gradually declines 25 .…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 95%
“…CSP induces higher bone turnover independent of renal function, decreases osteoblast proliferation, and decreases magnesium stores, important for vitamin D hydroxylation [65]. Recently, systemic lupus patients treated with CSP alone were found to have increases of FGF 23, which correlated with CSP cumulative dose, possibly etiologic in bone loss [66]. It remains debatable whether GVHD itself or its treatment in the form of glucocorticoid or cyclosporine has the greatest impact on bone health.…”
Section: Role Of Glucocorticoids and Calcineurin Inhibitorsmentioning
confidence: 99%